B-lymphocyte responses to trinitrophenyl-conjugated Ficoll: requirement for T lymphocytes and Ia-bearing adherent cells. - Letvin, N L (1981)
These studies were done to characterize the cellular requirements for B-lymphocyte responses to the haptenated polysaccharide trinitrophenyl-conjugated Ficoll. By using an in vitro microculture system, it was demonstrated that hapten-specific anti-trinitrophenyl-conjugated Ficoll plaque-forming cell responses by B lymphocytes require Ia-bearing adherent accessory cells and Thy 1+ Lyt 1+2- nylon wool-nonadherent (T) lymphocytes. Such T cells could be primed in vivo with nonderivatized Ficoll to show carrier-specific helper cell function for derivatized Ficoll responses in vitro. The implications of these findings for our understanding of b-lymphocyte triggering by so-called T-independent antigens are discussed.